The effect of high intensity interval training on CTGF and RXFP1 genes expression of heart tissue and SGPT liver enzyme in rats with fatty liver - Masoud Hamzehloo; Mania Roozbayani (Journal of Exercise & Organ Cross Talk, 2022)
This study investigated the effect of high intensity interval training on CTGF and RXFP1 genes expression of heart tissue and SGPT liver enzyme in rats with fatty liver. 48 male Wistar rats (200-250 g) were divided randomly into the following 6 groups: Healthy base group (BH), base Steatosis group (BS), Healthy HIIT group (HIIT), Steatosis HIIT group (SHIIT), Healthy control group (CH), control Steatosis group (CS). Rats in the fatty liver group received oral tetracycline daily for two weeks. Rats in the training groups were also trained for 5 weeks / five days. Both BS and BH groups sacrificed at the end of the 2nd week. CS and training groups sacrificed at the end of 5th week and heart tissue samples were taken to examine CTGF, RXFP1, and SGPT genes expression. The results of the study showed that he amounts of SGPT in BS and CS groups were meaningfully higher than those in the other 4 groups. The level of this enzyme in SHIIT and HIIT groups was significantly lower than that in the fatty liver groups. The RXFP1 gene expression in CS, BS and SHIIT groups were significantly higher than those in the other 3 groups. Thus, it can be claimed that fatty liver increased cardiac fibrosis factors but by reducing these factors HIIT was able to prevent the process of cardiac fibrosis from liver Steatosis; therefore, HITT can be used as a new method to Cardiac rehabilitation of patients.